2018
DOI: 10.5267/j.dsl.2018.1.004
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a mini-grid business model for developing countries using CRITIC-TOPSIS with interval type-2 fuzzy sets

Abstract: The growth in renewable energy study has resulted in the expansion of mini-grids projects across different communities in developing countries. However, there is a need to ensure that a suitable business model is selected during the provision of mini-grid services in developing countries. This study presents a framework for ranking mini-grid business models. The proposed framework is a multi-criteria multi-decision (MCMD) making tool. The framework combines Criteria Importance Through Inter-criteria Correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 41 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Business models' frameworks for mini-grid in developing countries, using Nigeria as a case study, are proposed in [113], considering four business models: government, private, public-private, and community-based. Two frameworks were proposed, "Technique for Order Performance by Similarity to Ideal Solution" (TOPSIS) and "Weighted Aggregated Sum Product Assessment" (WASPAS).…”
Section: Business Models In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Business models' frameworks for mini-grid in developing countries, using Nigeria as a case study, are proposed in [113], considering four business models: government, private, public-private, and community-based. Two frameworks were proposed, "Technique for Order Performance by Similarity to Ideal Solution" (TOPSIS) and "Weighted Aggregated Sum Product Assessment" (WASPAS).…”
Section: Business Models In Developing Countriesmentioning
confidence: 99%
“…This figure is built based on the included papers, and they have been considered as the core of literature classification. [1,[7][8][9]12,18,23,25,26,[29][30][31][32]37,40,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][98][99][100][101][102][103][104][105][107][108][109][110][111][112][113].…”
Section: Future Workmentioning
confidence: 99%
“…TOPSIS Despite the improvements in multi-criteria tools, -TOPSIS method ease of application, and best and worst solutions consideration continues to increase its acceptance among (37) Fuzzy-AHP Construction management Ighravwe and Oke (29) Fuzzy-entropy method Maintenance management Sremac et al (38) SWARA Logistic management Alam et al (39) Fuzzy AHP Service providers -ITC researchers (40). Because of this, literature in different disciplines, such as engineering, management, science and others, show the results that are generated using TOPSIS (28,40). While this sound interesting, there is a need to jump-start to apply TOPSIS in LFG analysis because other energy domains (e.g.…”
Section: Make Inferencementioning
confidence: 99%
“…However, there is sparse information on the aggregation of experts' judgment for a non-residential building. For instance, the benefit of using multicriteria tools in energy study was demonstrated by Ighravwe and Babatunde (2018). They attempt to identify a renewable energy business model for developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%